Search for direct production of electroweakinos in final states with one lepton, jets and missing transverse momentum in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2023)
Searches for electroweak production of wino-like chargino pairs, $$ {\overset{\sim }{χ}}_1^{+}{\overset{\sim }{χ}}_1^{-} $$, and of wino-like chargino and next-to-lightest neutralino, $$ {\overset{\sim }{χ}}_1^{± }{\overset{\sim }{χ}}_2^0 $$, are presented. The models explored assume that the charginos decay into a W boson and the lightest neutralino, $$ {\overset{\sim }{χ}}_1^{±}→ W^{± }{\overset{\sim }{χ}}_1^0 $$. The next-to-lightest neutralinos are degenerate in mass with the chargino and decay to $$ {\overset{\sim }{χ}}_1^0 $$and either a Z or a Higgs boson, $$ {\overset{\sim }{χ}}_2^0→ Z{\overset{\sim }{χ}}_1^0 $$or $$ h{\overset{\sim }{χ}}_1^0 $$. The searches exploit the presence of a single isolated lepton and missing transverse momentum from the W boson decay products and the lightest neutralinos, and the presence of jets from hadronically decaying Z or W bosons or from the Higgs boson decaying into a pair of b-quarks. The searches use 139 fb−1 of $$ \sqrt{s} $$= 13 TeV proton-proton collisions data collected by the ATLAS detector at the Large Hadron Collider between 2015 and 2018. No deviations from the Standard Model expectations are found, and 95% confidence level exclusion limits are set. Chargino masses ranging from 260 to 520 GeV are excluded for a massless $$ {\overset{\sim }{χ}}_1^0 $$in chargino pair production models. Degenerate chargino and next-to-lightest neutralino masses ranging from 260 to 420 GeV are excluded for a massless $$ {\overset{\sim }{χ}}_1^0 $$for $$ {\overset{\sim }{χ}}_2^0→ Z{\overset{\sim }{χ}}_1^0 $$. For decays through an on-shell Higgs boson and for mass-splitting between $$ {\overset{\sim }{χ}}_1^{± }/{\overset{\sim }{χ}}_2^0 $$and $$ {\overset{\sim }{χ}}_1^0 $$as small as the Higgs boson mass, mass limits are improved by up to 40 GeV in the range of 200-260 GeV and 280-470 GeV compared to previous ATLAS constraints.
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 09.08.2024